Facing Campus Challenges: Self-Compassion as the Key to Adjustment for New Students - Joane Elisabeth Prasetia, Ivana; Astikasari, Heru (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
The transition from school to college is often challenging for new students, which can affect their psychological well-being. Good adjustment in the campus environment is essential to reduce anxiety and increase life satisfaction. This study aims to identify and analyze the relationship between self-compassion and adjustment in the college environment in new students. The approach used is quantitative with a correlational design. The subjects of the study were 103 new students of Satya Wacana Christian University class of 2024, who were selected using convenience sampling techniques. Data were collected through a questionnaire to measure the level of self-compassion and adjustment. Data analysis using Spearman's Rank Correlation showed a significant positive relationship between self-compassion and adjustment, with a correlation coefficient of r = 0.588 and a significance level of p = 0.000 (p < 0.05). These findings indicate that increased self-compassion can contribute to better adjustment among new students. Therefore, it is important to develop strategies that can increase self-compassion as part of a support program for new students, to help them adapt to the college environment.Masa transisi dari sekolah ke perkuliahan seringkali menjadi tantangan bagi mahasiswa baru, yang dapat memengaruhi kesejahteraan psikologis mereka. Penyesuaian diri yang baik di lingkungan kampus sangat penting untuk mengurangi kecemasan dan meningkatkan kepuasan hidup. Penelitian ini bertujuan untuk mengidentifikasi dan menganalisis hubungan antara self-compassion dan penyesuaian diri di lingkungan perkuliahan pada mahasiswa baru. Pendekatan yang digunakan adalah kuantitatif dengan desain korelasional. Subjek penelitian adalah 103 mahasiswa baru Universitas Kristen Satya Wacana angkatan 2024, yang dipilih menggunakan teknik convenience sampling. Data dikumpulkan melalui kuesioner untuk mengukur tingkat self-compassion dan penyesuaian diri. Analisis data menggunakan Spearman's Rank Correlation menunjukkan adanya hubungan positif yang signifikan antara self-compassion dan penyesuaian diri, dengan koefisien korelasi r = 0.588 dan tingkat signifikansi p = 0.000 (p < 0.05). Temuan ini mengindikasikan bahwa peningkatan self-compassion dapat berkontribusi pada penyesuaian diri yang lebih baik di kalangan mahasiswa baru. Oleh karena itu, penting untuk mengembangkan strategi yang dapat meningkatkan self-compassion sebagai bagian dari program dukungan bagi mahasiswa baru, guna membantu mereka beradaptasi dengan lingkungan perkuliahan.